The Globalization Paradox: Democracy and the Future of the World Economy (an excerpt) - Rodrik, Dani (Journal of Economic Sociology, 2014)
From trade monopolies in XVIIcentury empires to modern institutions such as WTO, International Monetary Fund and World Bank, countries used different tools to gain advantages from globalization. Economic narratives of those times, including Gold Standard, the Bretton Woods regime, the “Washington Consensus”, were considered to be an overwhelming success as well as a great fail. Challenging the common views on globalization, Dani Rodrik suggests a new narrative indicating the insurmountable contradiction: we cannot simultaneously have democracy, national state and economic globalization. When social mechanisms of democracy inevitably meet globalization’s requirements, national interests have to come to the fore. Combining fascinating historic evidences with sound economic analysis, the author argues for curbing globalization with the help of international rules allowing standing against global challenges that we face in trade, finance and labour markets. The journal “Economic Sociology” publishes the introduction (“Recasting Globalization’s Narrative”) to the book “The Globalization Paradox” by D. Rodrik. In the introduction, the author indicates the research problem and elaborates his approach to its solution. Rodrik considers his approach to be an alternative to the shared views of economists and politicians, calling for full support of globalization. The author’s narrative is based on two ideas: (1) markets and governments are compliments, not substitutes; (2) there are many models of capitalism, which can contribute to economic growth.